Керування посадкою літаків за умов підвищення інтенсивності повітряного руху - Волошенюк, Д.О.; Павлова, С.В. (Управляющие системы и машины, 2017)
Найбільш відповідальним і складним етапом при зміні режиму польоту, психофізіологічних навантаженнях і швидкоплинністю є посадка повітряних кораблів. Метою підвищення безпеки польотів і розширення можливостей застосування авіації в різних умовах є вдосконалення систем посадки і навігаційного забезпечення літальних апаратів. Наиболее ответственным и сложным этапом при изменении режима полета, психофизиологических нагрузках и быстротечностью есть посадка воздушных судов. Цель повышения безопасности полетов и расширения возможностей применения авиации в различных условиях – совершенствование систем посадки и навигационного обеспечения летательных аппаратов. Purpose: The scientific task of the developing methods, models and means of informational support of decision making for the construction of an optimal landing trajectory for further improvement of the airplane flight safety and upgrading of environmental and economic indicators of the aviation equipment use is relevant. Methods: In order to reduce the number of aviation events, ICAO's decision is made on the need to install an ILSupgraded ILS or microwave landing system (MLS) in airports at the airports. However, there are currently four types of landing systems that meet the requirements of ICAO and aviation experts must select one of them. These are the ILS, MLS and two completely different satellite landing systems. All four systems meet the requirements of ICAO for automatic landing systems for the XXI century. Results: Accordingly, the task is to create a system in the aviation industry that will allow: – quantitatively and qualitatively increase the level of environmental friendliness and efficiency of flights in aviation in general; – to substantially improve the safety of flights; – solve the problem of airport overload with air traffic intensity; – to increase the efficiency of the aviation equipment use, etc. Discussion: The perspective direction is the introduction of a satellite communication system, navigation and surveillance. Important parameters that characterize the landing systems (in addition to reliability requirements) are the accuracy of the determining navigational parameters, working area and range of action.